Understanding Microbial Divisions of Labor - Zhang, Zheren; Claessen, Dennis; Rozen, Daniel E. (Frontiers in Microbiology, 2016)
Divisions of labour are ubiquitous in nature and can be found at nearly every level of biological organization, from the individuals of a shared society to the cells of a single multicellular organism. Many different types of microbes have also evolved a division of labour among its colony members. Here we review several examples of microbial divisions of labour, including cases from both multicellular and unicellular microbes. We first discuss evolutionary arguments, derived from kin selection, that allow divisions of labour to be maintained in the face of non-cooperative cheater cells. Next we examine the widespread natural variation within species in their expression of divisions of labour and compare this to the idea of optimal caste ratios in social insects. We highlight gaps in our understanding of microbial caste ratios and argue for a shift in emphasis from understanding the maintenance of divisions of labour, generally, to instead focusing on its specific ecological benefits for microbial genotypes and colonies. Thus, in addition to the canonical divisions of labour between e.g reproductive and vegetative tasks, we may also anticipate divisions of labour to evolve to reduce the costly production of secondary metabolites or secreted enzymes, ideas we consider in the context of streptomycetes. The study of microbial divisions of labour offers opportunities for new experimental and molecular insights across both well-studied and novel model systems.